Cost-utility analysis of loxenatide versus DPP-4 inhibitors in Chinese patients with type 2 diabetes at high cardiovascular risk - Longbing Lai; Fengning Chuan; Qiuhong Huang; Na Xiong; Chuan Peng; Ruobei Zhao; Jianjuan Sun; Qiang Liu; Jiangang Lu (Frontiers in Public Health, 2026)
Background In China, many patients with type 2 diabetes mellitus (T2DM) face high cardiovascular risk and a heavy disease burden. Loxenatide, a once-weekly GLP-1 receptor agonist developed in China, is now listed for reimbursement, but evidence on its long-term cost-effectiveness is limited. The FIGHTING-2 study, presented at the 2026 ECIM, provided the first direct comparison of cardiovascular outcomes between loxenatide and a DPP-4 inhibitor (sitagliptin) in Chinese T2DM patients at high cardiovascular risk and supplied core efficacy parameters for this study. Objective Assess the long-term cost-utility of loxenatide (0.2 mg once weekly) versus sitagliptin (100 mg once daily) in high cardiovascular risk type 2 diabetes patients in China inadequately controlled with metformin, from the healthcare system perspective. Methods A five-state Markov model (event-free, myocardial infarction, stroke, heart failure, and death) was developed to simulate the natural disease progression of patients with type 2 diabetes at high cardiovascular risk. The model used a 1-year cycle length over a 40-year time horizon. Transition probabilities were estimated using the UKPDS 82 risk equations, and clinical efficacy inputs were obtained from the FIGHTING-2 study. Cost and utility parameters were derived from Chinese local literature and the National Reimbursement Drug List. The willingness-to-pay threshold was set at three times China’s per capita GDP in 2025 (299,100 CNY per QALY), and both costs and health outcomes were discounted at an annual rate of 5%. The incremental cost-effectiveness ratio (ICER) was calculated in the base-case analysis. One-way and probabilistic sensitivity analyses (1,000 Monte Carlo simulations) were conducted to assess the robustness of the results. Results In the base-case analysis, loxenatide showed an ICER of 82058.77 CNY per QALY compared with sitagliptin, which is well below the willingness-to-pay threshold (299,100 CNY per QALY). One-way sensitivity analysis showed that the ICER was most affected by the hazard ratio for heart failure and by loxenatide cost, but loxenatide remained cost-effective across all scenarios. Probabilistic sensitivity analysis indicated loxenatide was cost-effective in 100% of simulations and consistently generated additional QALYs, demonstrating robust model results. The scenario analysis also confirmed the robustness of the model results. Conclusion Loxenatide has a clear cost-utility advantage over sitagliptin in the treatment of Chinese patients with type 2 diabetes at high cardiovascular risk. These findings provide high-quality evidence to support clinical standardization, rational drug use, reimbursement policy decisions, and optimal allocation of healthcare resources for this patient population in China.